(untitled) (Research, Society and Development, 2021)
The search for therapeutic resources that add to the vaccine and are able to prevent and/or treat COVID-19 suggests vitamin D. Vitamin D is known to play several extra-skeletal roles in the body, particularly in the immune system. This review aims to address the current attributions and perspectives for the use of vitamin D in patients with COVID-19. The search was performed using the Medline (PubMed) database, between May and July 2021, regarding the physiological and immunological roles of vitamin D in respiratory infections, as well as its mechanisms of action, concerning COVID- 19. The results suggest a possible association between serum 25(OH)D concentrations and the clinical setting of COVID-19 (mortality, systemic inflammation, illness severity, mechanical ventilation requirement or admission to the ICU), although the studies found differ in the design, sample size and outcomes, mitigating an accurate between-trial comparison. Therefore, further studies with a well-defined design evaluating the role of vitamin D in the prevention and/or treatment of COVID-19 is still necessary.